Habitually Higher Dietary Glycemic Index During Puberty Is Prospectively Related to Increased Risk Markers of Type 2 Diabetes in Younger Adulthood - Goletzke, Janina (American Diabetes Association, 2013)
OBJECTIVE: Carbohydrate nutrition during periods of physiological insulin resistance such as puberty may affect future risk of type 2 diabetes. This study examined whether the amount or the quality (dietary glycemic index [GI], glycemic load [GL], and added sugar, fiber, and whole-grain intake) of carbohydrates during puberty is associated with risk markers of type 2 diabetes in younger adulthood. RESEARCH DESIGN AND METHODS: The analysis was based on 226 participants (121 girls and 105 boys) from the Dortmund Nutritional and Anthropometric Longitudinally Designed Study (DONALD) with an average of five 3-day weighed dietary records (range 2–6) during puberty (girls, age 9–14 years; boys, age 10–15 years) and fasting blood samples in younger adulthood (age 18–36 years) (average duration of follow-up 12.6 years). Multivariable linear regression was used to analyze the associations between carbohydrate nutrition and homeostasis model assessment–insulin resistance (HOMA-IR) as well as the liver enzymes alanine aminotransferase (ALT) and γ-glutamyltransferase (GGT) (n = 214). RESULTS: A higher dietary GI was prospectively related to greater values of HOMA-IR (P(trend) = 0.03), ALT (P(trend) = 0.02), and GGT (P(trend) = 0.04). After adjustment for sex, adult age, baseline BMI, and early life and socioeconomic factors as well as protein and fiber intake, predicted mean HOMA-IR values in energy-adjusted tertiles of GI were 2.37 (95% CI 2.16–2.60), 2.47 (2.26–2.71), and 2.59 (2.35–2.85). The amount of carbohydrates, GL, and added sugar, fiber, and whole-grain intake were not related to the analyzed markers. CONCLUSIONS: Our data indicate that a habitually higher dietary GI during puberty may adversely affect risk markers of type 2 diabetes in younger adulthood.